Design and fabrication of shear test rig for sandwich cores - Dahrul Akma, Mohd Sabri (2007)
This project is focused on redesign the current model of shearing testing instrument and it is also used for testing the shear in sandwich constructions in order of driving the need for efficient, sale cost effective and stability of sandwich core upon the shear loading. The device consists of two main components; a stationary upper platform and a lower platform that contains a base as stage. The principle of operation is that the tissue samples are affixed to both the upper and lower platforms using a thin layer of superglue then bathed in an appropriate physiological solution. The lower platform is moved relative to the fixed upper platform using the base stage in order to applied load. The test is performed by clamping a test specimens attached in a 20 millimeters width specimen between two metal fixtures. An upper punch is then forced through the base in the metal fixture causing shear along the edge of the facing. A universal testing machine is used to push the punch until shearing of the specimen occurs. The manufacturing process included in this project is cutting of material, machining, drilling, threading and finishing.